The Exchangeable relationship between The Financial Market Indices (Islamic and Traditional) - A Standard Study of the " LQ45 and JII Indices on the Indonesia Stock Exchange - Madahi, Mohamed; Tarkou, Mohamed (Milev Journal of Research and Studies, 2017)
The purpose of this paper is to examine the relation between traditional stock exchange of Indonesia LQ45 the Islamic one. Through the analysis of stock market indicators in general and Indonesia Stock Exchange in particular, in addition to assessing self-gradient beam model and the analysis of functions response and components to predict the two indicating errors contrast. The study concluded that there is a mutual influence of the two indicators but the degree of vulnerability and response to traditional index (93.08%) is greater than Islamic index (4.85%) as well as large conventional index fluctuations comparing to the Islamic index that is stable.